Antiobesity, hepatoprotective and anti-hyperglycemic effects of a pharmaceutical formulation containing Cecropia pachystachya Trécul in mice fed with a hypercaloric diet. (15th November 2021) - Campos, Mara Lúcia de; Castro, Marina Bento de; Campos, Artur Domingos; Fernandes, Maria Fernanda; Conegundes, Jéssica Leiras Mota; Rodrigues, Matheus Nehrer; Mügge, Fernanda Lins Brandão; Silva, Aristóbolo Mendes da; Sabarense, Céphora Maria; Castañon, Maria Christina Marques Nogueira; Andreazzi, Ana Eliza; Scio, Elita
Abstract: Ethnopharmacological relevance: The leaves of Cecropia pachystachya Trécul (Urticaceae), known as embaúba, are used as hypoglycemic and for weight reduction in Brazilian traditional medicine. Aim of the study: This study investigated the effects of a pharmaceutical formulation (ECP20) containing C. pachystachya extract on some metabolic alterations caused by a hypercaloric diet in mice. Material and methods: Mice were randomly fed with a standard or hypercaloric diet and orally treated with ECP20 or vehicle for 13 weeks. Subsequently, adiposity, glucose intolerance, and the presence of nonalcoholic fatty liver disease were assessed. Adipose tissue and liver were collected after euthanasia and frozen at −80 °C for histological and antioxidant analyzes. The effect of ECP20 on the differentiation of 3T3-L1 pre-adipocytes was also investigated. Results: Animals treated with ECP20 showed less weight gain, reduced glycemia, glucose tolerance restored, and hepatoprotective effect. Also, ECP20 presented significant in vivo antioxidant activity. Treatment of 3T3-L1 preadipocytes with ECP20 did not inhibit cellular differencing. Conclusions: Therefore, ECP20 presented promising effects in the control of obesity and related disorders. Considering that glucose intolerance and hyperglycemia are strong evidence for the development of type 2 diabetes, the findings corroborated the traditional use of C. pachystachya to treat this disease. The chlorogenic acid and the flavonoids orientin and iso-orientin, present in the extract, might be involved in the activities found. Graphical abstract: Image 1